2020
DOI: 10.1002/lary.29156
|View full text |Cite
|
Sign up to set email alerts
|

Voice‐Related Quality of Life Is Associated with Postoperative Change in Subglottic Stenosis

Abstract: Objectives To characterize the impact of subglottic stenosis (SGS) on voice‐related quality of life (V‐RQOL) and quantify the effect of treatment on voice outcomes. Study Design Case series. Methods Retrospective review of SGS patients treated from 1996 to 2018 at a single institution to assess for 1) V‐RQOL association with individual patient cumulative treatment number and 2) V‐RQOL correlation with treatment type, time between treatments, and degree of stenosis. Analysis included both parametric and nonpara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Our findings demonstrate a significant pitch reduction for female voices following CTR, similar to other studies. 3,5,10,12,17 The serial acoustic measures show that the early postoperative pitch reduction is not permanent. Although most patients' F0 will remain below the preoperative F0 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrate a significant pitch reduction for female voices following CTR, similar to other studies. 3,5,10,12,17 The serial acoustic measures show that the early postoperative pitch reduction is not permanent. Although most patients' F0 will remain below the preoperative F0 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SGS also have a high prevalence of voice disorders, 4 possibly due to airflow turbulence 5 . Voice generally improves with endoscopic dilation of SGS 5‐8 . If open airway reconstruction is required, the current standard approach is cricotracheal resection, where the anterior cricoid cartilage is removed, and the cricothyroid muscles are either transected or repositioned 9‐11 .…”
mentioning
confidence: 99%
“…5 Voice generally improves with endoscopic dilation of SGS. [5][6][7][8] If open airway reconstruction is required, the current standard approach is cricotracheal resection, where the anterior cricoid cartilage is removed, and the cricothyroid muscles are either transected or repositioned. [9][10][11] However, numerous studies have shown that cricotracheal resection is associated with worsened postoperative subjective and objective voice outcomes.…”
mentioning
confidence: 99%